The Level of Utilization of Small Pelagic Fish Resources in Buton Regency, Southeast Sulawesi - Akbar, Aditya; Rasyid, Abdul; Nelwan, Alfa Filep Petrus (Hasanuddin University, 2023)
Management of small pelagic fish resources is one of the efforts to prevent a decrease in the carrying capacity of small pelagic fish resources which has continued to experience a decline in production capacity in Buton Regency since the last 5 years since 2016. This study aims to analyze CPUE (Catch per Unit Effort), sustainable potential (MSY) and level of utilization and level of exploitation so that it can become information for managing the utilization of small pelagic fish resources. The research method used analysis of the level of utilization and level of effort based on statistical data on fisheries production for the 2016-2020 period. The results of this study indicate that there is a relationship between CPUE and fishing effort, namely a decrease in CPUE of 0.4092 tons for every increase of effort of 1 effort, optimum catch value (CMSY) of 9447.04 tons per year, and optimum effort value (EMSY) of 152 attempts per year, the utilization rate is still below CMSY with an average of 7557.64 tons and the utilization rate has exceeded EMSY with an average of 178 units per year. The average value of the utilization rate for small pelagic fish in Buton Regency is 94.56%, meaning that it has exceeded the Total Allowed Catch (TAC) but not exceeded the MSY value, while the average effort level is 116.84%. This means that fishermen's catches can still be optimized, but may not exceed MSY, which is 9447.04 tons per year. Trends in the level of utilization and effort level of small pelagic fish resources in the last five years indicate that the utilization rate of small pelagic fish resources has decreased in line with increasing levels of exploitation each year.